2018
DOI: 10.1111/jai.13763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphenol A toxicity on growth performance, biochemical variables, and oxidative stress biomarkers of Nile tilapia,Oreochromis niloticus(L.)

Abstract: Bisphenol A (BPA) is one of the industrial chemical compound which is used in the production of polycarbonate plastics and epoxy resins. BPA is used throughout the world and it could enter the aquatic ecosystems causing serious problems. To evaluate the potential effects of BPA toxicity on Nile tilapia, Oreochromis niloticus (L.) performance, its lethal concentration (LC50) was determined and it was 13.13 µg/L. After that, fish (33.9 ± 0.55 g/fish) were exposed to 0.0, 1.64, or 3.28 µg/L of BPA for 6 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 92 publications
3
15
0
Order By: Relevance
“…Catfish exposed to BPA exhibited hypoproteinaemia, hypoalbuminaemia, and hypoglobulinaemia compared to the control ones. These results agreed with that documented in African catfish after pesticide exposures (Hamed, 2016;Marzouk et al, 2012;Sayed and Hamed, 2017;Abdel-Tawwab and Hamed, 2018). The depletion of serum total protein, albumin, and globulin in the BPA-exposed fish may be a result of dysfunctions of the liver and kidneys (Giron-Pérez et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Catfish exposed to BPA exhibited hypoproteinaemia, hypoalbuminaemia, and hypoglobulinaemia compared to the control ones. These results agreed with that documented in African catfish after pesticide exposures (Hamed, 2016;Marzouk et al, 2012;Sayed and Hamed, 2017;Abdel-Tawwab and Hamed, 2018). The depletion of serum total protein, albumin, and globulin in the BPA-exposed fish may be a result of dysfunctions of the liver and kidneys (Giron-Pérez et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The aquatic ecosystems are exposed to BPA through the urban sanitation, petrochemical industry discharge, and landfill leachates causing a severe problems to the aquatic organism's health (Flint et al, 2012;Rubin, 2011). Thus, its detrimental effects on aquatic animals have also received great concern (Buxton and Kolpin, 2005;Huang et al, 2012;Abdel-Tawwab and Hamed, 2018).…”
mentioning
confidence: 99%
“…LPO is a highly destructive process that increases the rigidity and decreases the fluidity of cellular membranes [53]. It has been reported that the levels of MDA increased as a result of oxidation of lipoprotein and lipids in cell membranes during oxidative stress [47,54]. The current results showed that the level of MDA in the gills of all Cu-exposed fish were not significantly different with the control.…”
Section: Discussionsupporting
confidence: 41%
“…Our results suggest that Cu exposure might significantly increase free radicals in the first few days and lead to the production of ROS, causing oxidative stress in fish. It is likely that the increase of SOD and CAT was an adaptive response of the animal to Cu toxicity and it served to neutralize the impact of increased ROS generation [31,33,46,47]. Carvalho et al [48] revealed that SOD and CAT had prominent roles in the scavenging of free radicals to protect the organisms from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate this process, we conducted a meta-analysis of existing literature to quantify the effects of BPA on aquatic organisms. A meta-analytic approach is important particularly because the effects of BPA on biological functions can be context dependent, and different taxa and biological traits show different responses when exposed to BPA (Abdel-Tawwab & Hamed, 2018;Martínez et al, 2019;Staples, Woodburn, Caspers, Hall, & Klecka, 2002;Wright-Walters, Volz, Talbott, & Davis, 2011). Given the ongoing development of policies regarding the environmental consequences of EDCs (Canesi & Fabbri, 2015;Crain et al, 2007;Flint, Markle, Thompson, & Wallace, 2012), there is an urgent need to evaluate environmental concentrations and their impact on aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%